Preparation of acrylonitrile/acrylamide copolymer beads via a redox method and their adsorption properties after chemical modification - Md Jamil, Siti Nurul Ain; Khairuddin, Mastura; Daik, Rusli (Walter de Gruyter, 2015)
Poly(acrylonitrile-co-acrylamide) [poly(AN-co- AM)] was prepared via a redox method, with sodium bisulfite and potassium persulphate as the initiators. High yield was attained in up to 76% of monomer conversion within 3 h of reaction time. The copolymers were then chemically modified with hydroxylamine hydrochloride to obtain amidoxime functional groups in the polyacrylonitrile (PAN) system. The role of the amidoxime group is to form a chelating ion-exchange network based on acrylonitrile for the adsorption of heavy metal ions in aqueous solution. Based on the Fourier transform infrared spectra, the appearance of a strong band at the regions of 1680 and 3300–3400 cm-1 due to the stretching vibration of C=O and NH2 groups, respectively, confirmed the copolymerization of acrylamide into the PAN system. In the case of modified copolymers, there was an appearance of broad bands at the regions of ∼3300 and ∼900 cm-1, which corresponded to the stretching vibrations of O-H and =N-O, respectively, from the oxime group. The scanning electron microscopy showed that the average size of the copolymer particles was ∼149 nm, and the average size increased to ∼217 nm in the case of the modified copolymer. The amidoximed poly(AN-co-AM) was analyzed by inductively coupled plasma to investigate its adsorption behavior toward Cu(II).